Tuberculosis on the rise in southern Mozambique (1997–2012). Issue 3 (23rd March 2017) - García-Basteiro, Alberto L.; Miranda Ribeiro, Rafaela; Brew, Joe; Sacoor, Charfudin; Valencia, Salomé; Bulo, Helder; Cobelens, Frank; Macete, Eusebio
Tuberculosis (TB) remains an important public health concern and a leading cause of disease and death worldwide. Mozambique is one of the few high-burden countries where incidence rates have not improved in recent years. The estimated TB incidence rate in 2014 was 552 cases per 100 000 population and the estimated case detection rate is very low at just around 39% [1, 2]. The National Tuberculosis Control Programme (NTP) in Mozambique was launched in 1977 and expanded nationwide in 1985 [3]. The TB patient registration system began in 1984 and short-course therapy followed in the late eighties [3, 4], despite a civil war which resulted in a shortage of qualified medical staff and supplies, and fragile deployment systems. By the year 2000, the Directly Observed Therapy, Short-Course (DOTS) strategy had complete coverage in all districts of Mozambique [4]. In Manhiça District, Mozambique, tuberculosis incidence rates underwent a 3-fold increase over 16 years (1997–2012) http://ow.ly/mkWG306wvGb